1973
DOI: 10.1002/chin.197317125
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: NACHBARGRUPPENBETEILIGUNG BEI DER UMSETZUNG EINIGER TRIARYLPHOSPHINE MIT BENZYLCHLORID

Abstract: Die Geschwindigkeit der Bildung der Triaryl‐benzylphosphoniumchloride (III) aus den Triarylphosphinen (I) und Benzylchlorid (II) in Benzol/Methanol wird durch ortho‐ständige Methoxyreste in den Phenylkernen (If), (Ih) und (Ik) deutlich erhöht, während ortho‐ständige Methylgruppen (Ib) und (Id) eine merkliche Verringerung der Reaktionsgeschwindigkeit verursachen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1980
1980
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This arose some years ago, when we reported on a curious phenomenon in the Wittig reactions of triphenylphosphonium benzylides with ortho -substituted benzaldehydes. Strong ortho -effects from substituents on phosphorus were already well known through the work of McEwen and co-workers, , and these had been extended to the Wittig reaction, although with conflicting results. , It was also known that Z -selectivity in stilbene synthesis could be induced by ortho -substituents with heteroatom lone pairs on the aldehyde. , However, remarkably, we found that this latter Z -selectivity could be substantially augmented by an additional ortho -substituent on the benzylide, despite the fact that such a substituent would ordinarily lead to E -selectivity. This counter-intuitive cooperative effect was strong enough to be preparatively useful ( Z / E up to 95:5), and the resulting Z -2,2′-disubstituted stilbenes have been used to good effect in synthesis by others. , At the time, we rationalized the results within the cycloaddition mechanism by proposing that the increased Z -selectivity arose from the induction by the ortho -heteroatom of a lower energy TS in the kinetically controlled cycloaddition step leading to a lower energy cis -OPA.…”
Section: Preliminary Remarks On the Evaluation Of Kinetic Diasterosel...mentioning
confidence: 67%
See 1 more Smart Citation
“…This arose some years ago, when we reported on a curious phenomenon in the Wittig reactions of triphenylphosphonium benzylides with ortho -substituted benzaldehydes. Strong ortho -effects from substituents on phosphorus were already well known through the work of McEwen and co-workers, , and these had been extended to the Wittig reaction, although with conflicting results. , It was also known that Z -selectivity in stilbene synthesis could be induced by ortho -substituents with heteroatom lone pairs on the aldehyde. , However, remarkably, we found that this latter Z -selectivity could be substantially augmented by an additional ortho -substituent on the benzylide, despite the fact that such a substituent would ordinarily lead to E -selectivity. This counter-intuitive cooperative effect was strong enough to be preparatively useful ( Z / E up to 95:5), and the resulting Z -2,2′-disubstituted stilbenes have been used to good effect in synthesis by others. , At the time, we rationalized the results within the cycloaddition mechanism by proposing that the increased Z -selectivity arose from the induction by the ortho -heteroatom of a lower energy TS in the kinetically controlled cycloaddition step leading to a lower energy cis -OPA.…”
Section: Preliminary Remarks On the Evaluation Of Kinetic Diasterosel...mentioning
confidence: 67%
“…This results in a three-center, four-electron (3c4e) bond, with the acceptor orbital being one of the P–C bond σ* orbitals, analogous to the (orthogonal) interaction forming the P–O bond. The proposal of such a through-space interaction has long-time precedent in organophosphorus chemistry, having been used most notably by McEwen and co-workers in simple rationalizations of the rates of quaternization of ortho -substituted arylphosphines and ω- N,N -dimethylaminoalkylphosphines and hydrolysis of ortho -substituted arylphosphonium salts. , More recently, similar through-space interactions have been proposed to explain O–Se peri -interactions in 1,8-substituted naphthalenes , and anthroquinones and large long-range PP coupling constants in 1,8-diphosphanaphthalenes, a phosphorus-containing carborane, tetraphosphine ferrocenyl complexes, biaryl bisphosphines, and calix[4]­arene bisphosphites …”
Section: Reactions Of Benzaldehydesmentioning
confidence: 99%
“…Three lines of support for this concept have been offered. (1) An X-ray diffraction study of benzyl(2-methoxyphenyl)diphenylphosphonium bromide has revealed that the P-0 distance is substantially shorter than the sum of the van der Waals radii of phosphorus and oxygen. Furthermore, the bond angles indicate that the o-methoxyphenyl group is actually leaning toward the phosphorus in order to facilitate a P-0 bonding interaction, and energy minimization calculations, in which the total steric energy is made up primarily of bond stretching energies and van der Waals nonbonded interactions, also indicate that a weak P-O bonding interaction exists.…”
Section: Introductionmentioning
confidence: 99%